The small protein CydX is required for function of cytochrome bd oxidase in Brucella abortus - Sun, Yao-Hui; de Jong, Maarten F.; den Hartigh, Andreas B.; Roux, Christelle M.; Rolan, Hortensia G.; Tsolis, Renee M. (Frontiers in Cellular and Infection Microbiology, 2012)
A large number of hypothetical genes potentially encoding small proteins of unknown function are annotated in the Brucella abortus genome. Individual deletion of 30 of these genes identified four mutants, in BAB1_0355, BAB2¬_0726, BAB2_0470 and BAB2_0450, that were highly attenuated for infection. BAB2_0726, a YbgT-family protein located at the 3’ end of the cydAB genes encoding cytochrome bd ubiquinal oxidase, was designated cydX. A B. abortus cydX mutant lacked cytochrome bd oxidase activity, as shown by increased sensitivity to H2O2, decreased acid tolerance and increased resistance to killing by respiratory inhibitors. The C terminus, but not the N terminus, of CydX was located in the periplasm, suggesting that CydX is an integral cytoplasmic membrane protein. Phenotypic analysis of the cydX mutant therefore suggested that CydX is required for full function of cytochrome bd oxidase, possibly via regulation of its assembly or activity.